The Role of Chess in the Intellectual Development of Children - Stegariu Vlad-Ionuț; Popușoi Simona Andreea; Abalașei Beatrice Aurelia; Trofin Florin Petruț; Honceriu Cezar (ALTIUS ACADEMY Foundation - Faculty of Physical Education and Sports, 2021)
It is well known, although a challenge for the researchers, that chess players tend to have superior intellectual abilities and the idea that chess practice makes people more intelligent became more and more popular. The aim of the present study was to examine the effect of chess playing on the intellectualdevelopment of primary-class students. 67 children were initially tested (Stegariu, 2019) from whom only 27 of them were retested using the Raven Standard Progressive Matrices. 21 were originally inthe beginners group, and 6 of them migrated from the control group. Results indicated that chess playing had a significant effect on the SPM performance. The results are statistically significant (p=0.043<0.05) which shows their improvement. Conclusions of this study underlines the benefits of studying chess inschool with a focus on the children's' cognitive development.